Analisis keterampilan sosial peserta didik dalam pembelajaran tematik berbasis model cooperative learning kelas V sekolah dasar - Andini, Rista; Marmoah, Sri; Suharno, Suharno (Didaktika Dwija Indria, 2023)
The 2013 curriculum is a new paradigm in Indonesian curriculum that emphasizes knowledge and skills competencies. The learning approach is done through an integrative thematic model with one output in the form of social skills. Social skills are important skills in the 21st century because they contain the basics for solving problems that exist in the social environment. The purpose of this study is to analyze how the social skills of fifth grade students in thematic learning based on cooperative learning models. This research method is a descriptive qualitative research. The subjects of the study were students and fifth grade teachers of SDN Pajang IV Surakarta. Data collection techniques through observation, questionnaires, interviews and documentation. Validity through triangulation of sources and techniques as well as content validity by expert judgement. The aspects of social skills assessment consist of five aspects with the elaboration of 10 indicators. The research resulted that the social skills of students were categorized as good or in percentage of 76.66%.